WT1 expression is inversely correlated with MYCN amplification or expression and associated with poor survival in non‐MYCN‐amplified neuroblastoma. Issue 2 (21st October 2015) - Masserot, Caroline; Liu, Qingyuan; Nguyen, Eric; Gattolliat, Charles-Henry; Valteau-Couanet, Dominique; Bénard, Jean; Huber, Catherine; Ségal-Bendirdjian, Evelyne
Abstract : Neuroblastoma (NB) is the most common extra cranial solid tumor in childhood and the most frequently diagnosed neoplasm during infancy. A striking feature of this tumor is its clinical heterogeneity. Several tumor progression markers have been delineated so far, among which MYCN amplification, which occurs in about 25% of total NB cases, with the percentage increasing to 30% in advanced stage NB. Although MYCN amplification is strongly correlated with NB of poor outcome, the MYCN status cannot alone predict all cases of poor survival in NB. Indeed NB without MYCN amplification (about 70–80% of NB) are not always favorable. WT1 was initially identified as a tumor suppressor gene involved in the development of a pediatric renal tumor (Wilms' tumor). Here, we describe an inverse correlation between WT1 expression and MYCN amplification and expression. However and most notably, our results show that WT1 gene expression is associated with a poor outcome for patients showing non‐MYCN‐amplified tumors. Thus WT1 expression is clinically significant in NB and may be a prognostic marker for better risk stratification and for an optimized therapeutic management of NB. Highlights: An inverse correlation between WT1 and MYCN expressions is revealed in neuroblastoma (NB). High expression of WT1 is associated with lower survival in non‐MYCN‐amplified NB. Flat and substrate‐adherent NB cells express high levels of WT1. WT1 is potentially a prognostic marker in NB without MYCN amplification.